Morphological feature extraction of corn roots using deep learning - Fatemi, Ali; Inanlu, M.J.; Momin, Abdul; Grift, Tony (Rhizosphere, 2025)
The study of corn root morphology is critical for understanding root architecture, which directly influences water and nutrient uptake, plant stability, and overall yield performance. It also plays a crucial role in advancing crop breeding programs. Traditional methods of analyzing root morphology are often labor-intensive, time-consuming, and subject to variability. This research introduces a deep learning (DL)-based approach for the automated and precise extraction of morphological features from monochrome images of corn roots. While DL methods have been widely applied to various agricultural problems such as yield estimation, cultivar classification, and disease detection, its application to plant features, particularly root traits, remains limited. In this study, three DL architectures- EfficientNet_B0, DenseNet_121, and ResNet_50- were used to extract and predict 12 morphological features from both raw and background-subtracted side-view images of corn roots. The results showed that all three architectures performed similarly, with DenseNet_121 slightly outperforming the others in terms of coefficient of determination and normalized root mean square error (NRMSE) metrics for background-subtracted images (mean R2 0.9199 and mean NRMSE 0.0444), while EfficientNet_B0 showed superior performance with raw images (mean R2 0.9057 and mean NRMSE 0.0480). Importantly, no significant difference in architecture performance was observed between raw and background-subtracted images. The study shows the potential of end-to-end learning by providing a robust, automated tool for plant morphological feature extraction. •Introduces a deep learning-based approach for automated extraction of corn root morphology.•Compares three deep learning architectures (EfficientNet_B0, ResNet_50, DenseNet_121) for feature extraction.•DenseNet_121 achieved higher prediction accuracy with background-subtracted images.•The study highlights the potential of deep learning as an end-to-end approach for root morphological analysis in crop breeding programs.